Ecophysiological observations on Keoladeo National Park, Bharatpur (India) - Singh, R P; Agarwal, R M; Tiwari, Avinash (Journal of Wetlands Ecology, 2011)
Keoladeo National Park is a 'Ramsar site' which is flooded by Ajan bandh and is reserved for its high level of biodiversity. Owing to its global ecological, faunal and floral significance, it was declared a world heritage site in 1985. The total area i.e. 28.7 square km presents a variety of habitats i.e. marshy/wetlands, woodlands and grasslands etc. Wetlands support a variety of flora and fauna and have maximum biodiversity because of plenty of nutrients. However, wetlands may exhibit salinity due to upwelling of salts and that makes it a different site from the routine one. In order to evaluate the salinity status of the soil and its reflection on the vegetation, an analysis of soil and plants was carried out. For analysis three dominant plants of the Park viz. Acacia nilotica, Prosopis juliflora, and Mitragyna parvifolia were selected. Along with inorganic constituents, organic constituents of osmotica were also determined to evaluate their contribution under such conditions in plants. Key Words: Keoladeo National Park; Bharatpur; wetlands; Ramsar site; ecophysiological; salinity DOI: 10.3126/jowe.v4i0.2588 Journal of Wetlands Ecology, (2010) Vol. 4, pp. 43-68